2005
DOI: 10.2174/1568010054526359
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Production and Signaling in Inflammation

Abstract: Nitric oxide (NO) is recognized as a mediator and regulator of inflammatory responses. It possesses cytotoxic properties that are aimed against pathogenic microbes, but it can also have damaging effects on host tissues. NO reacts with soluble guanylate cyclase to form cyclic guanosine monophosphate (cGMP), which mediates many of the effects of NO. NO can also interact with molecular oxygen and superoxide anion to produce reactive nitrogen species that can modify various cellular functions. These indirect effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
626
0
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 844 publications
(663 citation statements)
references
References 191 publications
(240 reference statements)
23
626
0
14
Order By: Relevance
“…This indicates that it is a key contributor to the anti-inflammatory activity of rhubarb. NO is a well-known pro-inflammatory cytokine involved in many inflammatory diseases (Guzik et al, 2003) and is produced in high amounts by the iNOS protein that is induced by microbial products, such as LPS (Korhonen et al, 2005). Our data indicate that aloe-emodin inhibits the transcription and protein expression of iNOS.…”
Section: Discussionmentioning
confidence: 48%
“…This indicates that it is a key contributor to the anti-inflammatory activity of rhubarb. NO is a well-known pro-inflammatory cytokine involved in many inflammatory diseases (Guzik et al, 2003) and is produced in high amounts by the iNOS protein that is induced by microbial products, such as LPS (Korhonen et al, 2005). Our data indicate that aloe-emodin inhibits the transcription and protein expression of iNOS.…”
Section: Discussionmentioning
confidence: 48%
“…Excessive production of nitric oxide is thought to play a role in inflammatory diseases (reviewed in [1]). Nitric oxide is generated from L-arginine by the catalytic reaction of different isoforms of nitric oxide synthase (NOS), including neuronal NOS (nNOS), endothelial NOS (eNOS) and inducible NOS (iNOS).…”
Section: Introductionmentioning
confidence: 99%
“…It has cytotoxic and cytostatic effects, which are beneficial in host defence against pathogenic microbes. In inflammatory diseases, the regulatory, pro-inflammatory and destructive effects of NO modulate the responses also in host tissues (Moilanen et al, 1999;Abramson et al, 2001;Korhonen et al, 2005) and inhibitors of iNOS have been found to be beneficial in various models of inflammatory diseases (Vallance and Leiper, 2002). High amounts of NO are produced through the inducible nitric oxide synthase (iNOS) pathway in response to proinflammatory cytokines and bacterial products.…”
Section: Introductionmentioning
confidence: 99%
“…High amounts of NO are produced through the inducible nitric oxide synthase (iNOS) pathway in response to proinflammatory cytokines and bacterial products. Expression of iNOS has been shown to be regulated both at transcriptional and post-translational levels in activated macrophages, but many of the mechanisms are still unknown (MacMicking et al, 1997;Alderton et al, 2001;Kleinert et al, 2003;Aktan, 2004;Korhonen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%